Mini 3D transesophageal probe: technical advances and clinical applications - Monica Barki; Rebecca T. Hahn (Cardiovascular Ultrasound)
Abstract With the growing complexity of structural heart disease procedures, the need for advanced intraprocedural imaging has become increasingly critical. Transesophageal echocardiography remains the gold standard for procedural guidance but is associated with risks such as upper gastrointestinal tract injury and the need for general anesthesia for patient comfort and safety. Miniaturized three-dimensional transesophageal echocardiography (miniTEE) probes offer a promising solution by providing high-resolution imaging which could be performed under conscious sedation. Studies evaluating the miniTEE probe for safety, image quality, and ability to guide specific structural and non-structural heart disease procedures will be reviewed. The limitations and future developments will be discussed. Graphical abstract: smaller transesophageal echocardiography probes have a number of advantages and limitations. As the technology improves, the utilization of these probes will likely increase